2022
DOI: 10.1037/spy0000310
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of within-dyad interpersonal emotional influence in the ambulance service.

Abstract: Ambulance service personnel experience an array of emotions when working on shift. Nevertheless, there has been a lack of research to date regarding the interpersonal effects that frontline staff members’ emotional experiences and displays can have on their crewmates’ behavior and emotional state. This study used a critical realist research approach to explore the influential within-dyad effect of emotional exhibitions in frontline ambulance pairs. Ambulance service personnel (N = 18) were recruited to take pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…As the encoding and decoding of emotional expressions are general prerequisites for the social impact of emotions (van Kleef & Côté, 2022), it is worth mentioning evidence from other fields that highlight the importance of addressing the interaction between the sender and the receiver of emotional expressions. For example, a study in the ambulance service indicates that personnel may differ widely in their tendencies to express emotions during work, which may have a strong impact on the emotional state of others (Freemantle et al, 2022b). Moreover, in the military context, it was shown that the relationship between transformational leadership (i.e., a leadership style characterized by inspiration and encouragement) and the job involvement was stronger for those subordinates with a high emotional contagion susceptibility (Cheng et al, 2012).…”
Section: Antecedents Of Emotional Convergencementioning
confidence: 99%
“…As the encoding and decoding of emotional expressions are general prerequisites for the social impact of emotions (van Kleef & Côté, 2022), it is worth mentioning evidence from other fields that highlight the importance of addressing the interaction between the sender and the receiver of emotional expressions. For example, a study in the ambulance service indicates that personnel may differ widely in their tendencies to express emotions during work, which may have a strong impact on the emotional state of others (Freemantle et al, 2022b). Moreover, in the military context, it was shown that the relationship between transformational leadership (i.e., a leadership style characterized by inspiration and encouragement) and the job involvement was stronger for those subordinates with a high emotional contagion susceptibility (Cheng et al, 2012).…”
Section: Antecedents Of Emotional Convergencementioning
confidence: 99%
“…A unique feature of the journal is its focus on performance psychology, which includes sport and physical activity settings, but also in other performance domains as well. Recent examples include the development and evaluation of a novel resilience-enhanced reflection protocol within military settings (Chapman et al, 2022), a meta-analytic test of trust formation and development within swift starting action teams (Lines et al, 2022), an experimental study designed to examine the effects of goal types on cognitive performance (Pilcher et al, 2022), and a qualitative study designed to examine the interpersonal emotional experiences of ambulance service dyads when working shifts together (Freemantle et al, 2022). It is my hope that performance-based research conducted in such settings (e.g., military, health care, performing arts) will advance, but also be advanced by, innovative inquiry in sport and physical activity settings.…”
mentioning
confidence: 99%